Tools and challenges in the use of routine clinical data for antimicrobial resistance surveillance - Kathryn E. Holt; Megan E. Carey; Clare Chandler; James H. Cross; Zoe A. Dyson; Nicholas Furnham; Rebecca E. Glover; Mollie Virgo; Gwenan M. Knight (npj Antimicrobials and Resistance)
Abstract Routine clinical microbiology data are widely used for antimicrobial resistance (AMR) surveillance, but data availability and quality vary. In this Perspective, we explore the technical challenges of utilising routine data to inform action at various levels, and summarise emerging open-source technical solutions for hospital-level data collection, aggregation, and sharing. We highlight a need for agreed-upon data standards, and tools that support both facility-level and public health surveillance.